Robert Burns and pastoral poetry and improvement in late eighteenth-century Scotland - Leask, Nigel, 1958- (Oxford University Press, 2010)
This text restores the long marginalised Scottish poet Robert Burns to his rightful place as a major poet of the 18th century & Romantic period. It discusses his education as a farmer during the revolutionary period of 'improvement' in 18th-century Scotland, decision to write 'Scots pastoral' poetry, & influence on Wordsworth and Coleridge.